"A New Moonshot:" Exploring the Metaphoric Shift in American Cancer Discourse. Issue 4 (8th August 2021) - Wernecke, Christopher J.
ABSTRACT: In this essay, I contend that American cancer discourse is in the midst of a metaphoric shift away from war and its metaphors towards metaphors of space and space exploration. To better understand the rhetorical implications of this metaphoric shift, I draw upon several scholars including Lakoff and Johnson, Segal, Sontag, and Asen to examine a fuller enactment of these new metaphors as they manifest across political and policy discourses. I then conclude by advocating for the turn towards space and space exploration metaphors in American cancer discourse, arguing that it is the best alternative to challenge the negative hegemony of the martial metaphoric frame.